2011
DOI: 10.1007/s10459-011-9323-2
|View full text |Cite
|
Sign up to set email alerts
|

Students’ learning as the focus for shared involvement between universities and clinical practice: a didactic model for postgraduate degree projects

Abstract: In an academic programme, completion of a postgraduate degree project could be a significant means of promoting student learning in evidence- and experience-based practice. In specialist nursing education, which through the European Bologna process would be raised to the master's level, there is no tradition of including a postgraduate degree project. The aim was to develop a didactic model for specialist nursing students' postgraduate degree projects within the second cycle of higher education (master's level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…Similar suggestions can be found in the literature, where preparing the students to meet the expectations placed on a nurse in practice is a responsibility shared by universities and the healthcare system (Millberg et al, 2014;Öhlén et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar suggestions can be found in the literature, where preparing the students to meet the expectations placed on a nurse in practice is a responsibility shared by universities and the healthcare system (Millberg et al, 2014;Öhlén et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…To better understand nurses’ work in practice and to gain a better understanding of the importance of theorising practice, the participants in our study suggested that Master's students should conduct in‐depth degree projects linked to their workplace. Similar suggestions can be found in the literature, where preparing the students to meet the expectations placed on a nurse in practice is a responsibility shared by universities and the healthcare system (Millberg et al., 2014; Öhlén et al., 2012).…”
Section: Discussionsupporting
confidence: 53%
“…The research team met every month via the internet or through physical meetings. They also communicated through a special web portal adapted for the project [13] .…”
Section: Methodsmentioning
confidence: 99%